Relationship of runs of homozygosity with adaptive and production traits in a paternal broiler line - Marchesi, J. A.P. [UNESP]; Buzanskas, M. E.; Cantão, M. E.; Ibelli, A. M.G.; Peixoto, J. O.; Joaquim, L. B. [UNESP]; Moreira, G. C.M.; Godoy, T. F.; Sbardella, A. P. [UNESP]; Figueiredo, E. A.P.; Coutinho, L. L.; Munari, D. P. [UNESP]; et al. (Elsevier, 2018)
Genomic regions under high selective pressure present specific runs of homozygosity (ROH), which provide valuable information on the genetic mechanisms underlying the adaptation to environment imposed challenges. In broiler chickens, the adaptation to conventional production systems in tropical environments lead the animals with favorable genotypes to be naturally selected, increasing the frequency of these alleles in the next generations. In this study, ∼1400 chickens from a paternal broiler line were genotyped with the 600 K Affymetrix® Axiom® high-density (HD) genotyping array for estimation of linkage disequilibrium (LD), effective population size (Ne), inbreeding and ROH. The average LD between adjacent single nucleotide polymorphisms (SNPs) in all autosomes was 0.37, and the LD decay was higher in microchromosomes followed by intermediate and macrochromosomes. The Ne of the ancestral population was high and declined over time maintaining a sufficient number of animals to keep the inbreeding coefficient of this population at low levels. The ROH analysis revealed genomic regions that harbor genes associated with homeostasis maintenance and immune system mechanisms, which may have been selected in response to heat stress. Our results give a comprehensive insight into the relationship between shared ROH regions and putative regions related to survival and production traits in a paternal broiler line selected for over 20 years. These findings contribute to the understanding of the effects of environmental and artificial selection in shaping the distribution of functional variants in the chicken genome.
Keywords: animal breeding; Gallus gallus; inbreeding; oxidative stress; selection